Minimally invasive esophagectomy with non-invasive ventilation by laryngeal mask-assisted anesthesia for esophageal squamous cell carcinoma: case report - Che, Weibi; Zhong, Jian; Huang, Jiawei; Chen, Huilong; Feng, Caihou; Xie, Yujie; He, Haiquan; Chen, Ying; Li, Cui; Wu, Bomeng; Ding, Wei; Lin, Wanli (Frontiers in Oncology, 2024)
Minimally invasive esophagectomy for cancer surgery remains associated with significant morbidity and surgical complications across the globe. Non-intubation video-assisted thoracic surgery (NIVATS) has been successfully employed in lung resection in recent years, but there are few reported cases with regard to the safety and feasibility of this approach in radical esophagectomy for patients with esophageal cancers. We present 4 consecutive cases with esophageal squamous cell carcinoma (ESCC) who received minimally invasive McKeown’s esophagectomy under non-intubation general anesthesia from November 2022 to April 2023. All these patients were aged from 55 to 75 years old and were pathologically diagnosed with ESCC. All procedures of McKeown’s esophagectomy in these patients were completed with non-invasive ventilation by laryngeal mask-assisted anesthesia. Operation duration ranged from 185 to 395 minutes and the estimated blood loss ranged from 25 to 60 ml in these 4 cases. No severe hypoxia was observed and transient hypercapnia was resolved intraoperatively. None of them was converted to endotracheal intubation with mechanical ventilation or to thoracotomy. The number of retrieved lymph nodes in mediastinum were 21-27 and all patients received R0 surgery with pathological stage as T1bN0M0 to T3N2M0. There was no serious complication (Clavien-Dindo grade III-IV) observed perioperatively and they were all discharged 11-14 days after the surgery with resumption of oral feeding. They are all alive without tumor recurrence at the date of data collection. The safety and efficacy of minimally invasive esophagectomy with non-invasive ventilation by laryngeal mask-assisted anesthesia for patients with ESCC are warranted for explored in a larger cohort study.